(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2021)
Voltage sag and harmonics are frequently occurred problems related while, non linear loads are be placed. This effects the critical loads connected at same line of common coupling of the distribution line. Here this paper presents an overview to overcome the power quality issues and analysis of different harmonics and sag disturbing the distribution line by FACTS devices known as Distribution Static Compensator (D-STATCOM) . The control method of Unit Template Algorithm for reference current generation is proposed in this paper. The modle of distribution line and D-STATCOM are implemented by MATLAB-SIMULINK software.